Pharmacological effects of paeonol against endoplasmic reticulum stress and inflammation-induced endothelial dysfunction / Choy Ker Woon - Choy, Ker Woon (2018)
Endoplasmic reticulum (ER) stress and inflammation leads to endothelial dysfunction which are associated with the pathogenesis of cardiovascular diseases such as atherosclerosis, ischemic heart disease, cardiac hypertrophy and hypertension. Endothelial dysfunction is characterized by reduction of the endothelium-derived relaxing factors (EDRFs), particularly nitric oxide (NO), and/or an increase in endothelium-derived contracting factors (EDCFs), resulting in impairment of endothelium-dependent relaxation (EDR). Paeonol (20-hydroxy-40- methoxyacetophenone) is the most abundant phenolic component of Moutan cortex, the root of Paeonia suffruticosa Andrews which is widely used in traditional Chinese medicine. However, limited information is available concerning the pharmacological effects of paeonol in protecting against vascular endothelial dysfunction due to ER stress and inflammation. The present study investigates the pharmacological effects of paeonol against ER stress and inflammation-mediated endothelial dysfunction using in vitro, ex vivo and in vivo models. Our findings revealed that ex vivo and in vivo treatments with paeonol reversed the impaired EDR in C57BL/6J and peroxisome proliferator-activated receptor δ (PPARδ) wild-type mouse aortas following exposure with ER stress inducer, tunicamycin. Treatment with paeonol or tempol reversed the elevated blood pressure, ER stress and reactive oxygen species (ROS) as well as reduced NO bioavailability induced by tunicamycin in human umbilical vein endothelial cells (HUVECs), C57BL/6J and PPARδ wild-type mouse aorta. These protective effects of paeonol were diminished by co-incubation with PPARδ antagonist, GSK0660 and 5′ adenosine monophosphateactivated protein kinase (AMPK) antagonist, compound C as well as in aorta from PPARδ iv knockout mouse. These findings suggest that paeonol protects against tunicamycininduced endothelial dysfunction in mice by inhibiting ER stress and ROS production by elevating NO bioavailability via the AMPK/PPARδ pathway. The protective effect of paeonol was further examined against inflammation-induced endothelial dysfunction. Exposure of HUVECs to lipopolysaccharide (LPS), an inflammatory stimuli increased the protein expression of toll like receptor 4 (TLR4), bone morphogenic protein 4 (BMP4), BMP receptor type 1A (BMPR1A), nicotinamide adenine dinucleotide phosphate oxidase subunit 2 (NOX2), mitogen-activated protein kinases (MAPK), inducible nitric oxide synthase (iNOS) and cleaved caspase 3 and decreased the protein expression of phosphorylated endothelial nitric oxide synthase (eNOS). Co-treatment with paeonol reversed the LPS-induced inflammatory responses in HUVECs and in addition prevented the BMP4-induced apoptosis of the endothelial cells. In the mouse aorta, LPS impaired EDR was subsequently reversed by co-treatment with paeonol, noggin (BMP4 inhibitor), TAK242 (TLR4 inhibitor), apocynin (ROS scavenger), MAPK inhibitors and aminoguanidine (iNOS inhibitor). Blockade by BMP4 small interfering RNA (siRNAs) but not with TLR4 siRNA, abolished LPS-induced increases in BMP4 protein expression and vice versa. Silencing of TLR4 and BMP4 abolished the protective effects of paeonol on LPS-induced activation of cleaved caspase 3. The present findings imply that paeonol reduces LPS-induced endothelial dysfunction and cell apoptosis by inhibiting BMP4-triggered ROS production, independent of TLR4 signalling. Taken together, the results demonstrate the protective effects of paeonol against endothelial dysfunction induced by ER stress and inflammation. The present study further support other potential use of paeonol as a novel endothelial protective agent in cardiovascular diseases associated with ER stress and inflammation.